Freestanding electrochromic paper. Issue 41 (6th October 2016) - Malti, Abdellah; Brooke, Robert; Liu, Xianjie; Zhao, Dan; Andersson Ersman, Peter; Fahlman, Mats; Jonsson, Magnus P.; Berggren, Magnus; Crispin, Xavier
Abstract : A combination of nanofibrils and nanoparticles is used to fabricate polymer-based freestanding electrochromic materials which exhibit contrasts >20 in devices. Abstract : Electrochromic displays based on conducting polymers exhibit higher contrasts and are cheaper, faster, more durable, and easier to synthesize as well as to process than their non-polymeric counterparts. However, current devices are typically based on thin electrochromic layers on top of a reflecting surface, which limits the thickness of the polymer layer to a few hundred nanometers. Here, we embed a light-scattering material within the electrochromic material to achieve a freestanding electrochromic paper-like electrode (50 to 500 μm). The device is based on a cellulose composite combining PEDOT:PSS as the electrochromic material and TiO2 nanoparticles as the reflecting material. Owing to the excellent refractive properties of TiO2, this nanocomposite is white in the neutral state and, when reduced, turns blue resulting in a color contrast around 30. The composite has a granular morphology and, as shown by AFM, an intermingling of TiO2 and PEDOT:PSS at the surface. Variation of the amount of TiO2 within the composite material is shown to result in a trade-off in optical and electrical properties. A proof-of-concept freestanding electrochromic device was fabricated by casting all layers successively to maximize the interlayer conformation. This freestanding device was found to be stable for over 100 cycles when ramped between 3 and −3 V.